(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
With the rapid growth of information technology and the widespread use of digital devices, social engineering has become one of the most pressing challenges in today’s cybersecurity landscape. In simple terms, social engineering involves manipulating people by exploiting human psychology to carry out harmful activities. This review explores different types of social engineering threats across various environments, emphasizing how people rather than systems or technologies are often the weakest link in security. As a result, there's a growing need to boost awareness among users. One of the most effective ways to tackle this issue is through targeted training and educational programs. This paper discusses how creative and well-structured information security education can significantly improve user awareness and help reduce the number of cyber incidents.